Creativity as a key element of innovation in science and education - Супрун, А. Г.; Чухачова, В. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Attention is focused on the issues and understanding of the essence of modern life science and awareness of its importance as a primary element – the basis of the innovation system of the society. Implemented a philosophical analysis of the concept of "innovation", defined the historical and philosophical background of the formation of the main functions of science is characterized by the relationship of philosophy, science and innovation, as a direct result of the logical development of science. The urgency due to the specified topics design processes in the scientific, social, cultural, economic and political life of Ukraine and the world. It was found that in the new century science enters a new scientific worldview, formed under the influence of modern scientific and technological revolution and dramatically affect the change of reality and of man himself. Thanks to the creativity of the possibility of any progress, based can only be innovation. Creativity - is creation of new models and implement them through functional activity in material things or in physical models. Formation of a new socio-economic and political-legal reality is in direct proportion to the extent to which these processes are imbued strategy of innovation and synthesizing creative people how they will rule the principles of humanism, healthy criticism, social freedom, pluralism, high moral responsibility.